Tax-benefit microsimulation and income redistribution in Ecuador - H. Xavier Jara; Marcelo Varela (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
The aim of this paper is to explore the redistributive effects of taxes and benefits in Ecuador using two different approaches: direct use of reported taxes and benefits in household survey data, and use of simulated taxes and benefits obtained from ECUAMOD, the tax-benefit microsimulation model for Ecuador. Our results show that simulated taxes and social insurance contributions capture better the number of taxpayers and aggregate revenue amounts from official statistics than information taken directly from the data. Moreover, using reported data on taxes and social insurance contributions underestimates their redistributive effect in comparison with simulated policies. We discuss factors behind the differences between the two approaches and conclude with a discussion of the advantages offered by microsimulation for policy analysis.
Keywords: I32; I38; H24; D13; 330; taxes; benefits; microsimulation; Ecuador